Comparative study of alpha‐ and beta‐pinene effect on PTZ‐induced convulsions in mice. (25th October 2018) - Felipe, Cícero Francisco Bezerra; Albuquerque, Aline Mirely Sousa; de Pontes, João Luis Xavier; de Melo, José Ítalo Vieira; Rodrigues, Teresa Carolliny Moreira Lustoza; de Sousa, Ada Mirtes Pereira; Monteiro, Álefe Brito; Ribeiro, Ana Elisa da Silva; Lopes, Janice Pereira; de Menezes, Irwin Rose Alencar; de Almeida, Reinaldo Nóbrega
Abstract: Convulsions occur in response to a loss of balance between excitatory and inhibitory neurotransmitters, and the treatment for this condition consists in restore such lost balance. Many anticonvulsant drugs present side effects which may limit their use. This fact has stimulated the search for new sources of treatment from aromatic plants. Many monoterpenes commonly present in essential oils are known because of their anticonvulsant properties. The anticonvulsant effect of α‐ and β‐pinene, two structural isomers, is still little studied. Thus, the present work evaluated the anticonvulsant effect of α‐ and β‐pinene in pentylenetetrazole‐induced convulsions model. Initially, the oral LD50 for α‐ and β‐pinene was estimated. Following the oral administration, a mild sedation was observed and no deaths were recorded; the LD50 estimated for both monoterpenes was greater than 2 000 mg/kg, p.o. Further, animals were orally treated with α‐pinene (100, 200 and 400 mg/kg), β‐pinene (100, 200 and 400 mg/kg) and the equimolar mixture of α‐ and β‐pinene (400 mg/kg) and subjected to the pentylenetetrazole‐induced convulsions model. In this model, only the dose of 400 mg/kg of the compounds was able to significantly decrease the seizure intensity. The latency of first convulsion was significantly increased by the mixture of α‐ and β‐pinene (400 mg/kg). In addition, β‐pinene and the mixture of the two monoterpenes, both at a dose of 400 mg/kg, significantly increased the time of death of animals. The treatment with β‐pinene and the equimolar mixture of the two monoterpenes significantly reduced hippocampal nitrite level and striatal content of dopamine (DA) and norepinephrine (NE). Taken together, the results suggest that α‐pinene appears to be devoid of anticonvulsant action. This fact, however, seems to be dependent on the chemical structure of the compound, since pretreatment with the β‐pinene increased the time of death pf PTZ‐treated mice, which seems to depend on the ability of the compound to reduce nitrite concentration and NE and DA content, during the pentylenetetrazole‐induced seizure.